Synthesis and evaluation of condensed magnetic nanocrystal clusters with in vivo multispectral optoacoustic tomography for tumour targeting - Sarigiannis, Yiannis; Kolokithas-Ntoukas, Αrgiris; Beziere, Nicolas; Zbořil, Radek; Papadimitriou, Evangelia; Avgoustakis, Konstantinos; Lamprou, Margarita; Medrikova, Zdenka; Rousalis, Elias; Ntziachristos, Vasilis; Bakandritsos, Aristides (Biomaterials, 2016)
Colloidal clusters of magnetic iron oxide nanocrystals (MIONs), particularly in the condensed pattern (co-CNCs), have emerged as new superstructures to improve further the performance of MIONs in applications pertaining to magnetic manipulation (drug delivery) and magnetic resonance imaging (MRI). Exploitation of the advantages they represent and their establishment in the area of nanomedicine demands a particular set of assets. The present work describes the development and evaluation of MION-based co-CNCs featuring for the first time such assets: High magnetization, as well as magnetic content and moment, high relaxivities (r2 = 400 and r2* = 905 s(-1) mMFe(-1)) and intrinsic loss power (2.3 nH m(2) kgFe(-1)) are combined with unprecedented colloidal stability and structural integrity, stealth and drug-loading properties. The reported nanoconstructs are endowed with additional important features such as cost-effective synthesis and storage, prolonged self-life and biocompatibility. It is finally showcased with in vivo multispectral optoacoustic tomography how these properties culminate in a system suitable for targeting breast cancer and for forceful in vivo manipulation with low magnetic field gradients.
Keywords: doxorubicin; optoakustické techniky; Tomography, X-Ray Computed; nádory prsu; Mice; zvířata; prsy; Polyethylene Glycols; Breast Neoplasms; protinádorová antibiotika; myši nahé; Nanocrystal clusters; Theranostics; nanočástice; Nanoparticles; Breast; Hybrid colloids; Drug Delivery Systems; železité sloučeniny; Hyperthermia; polyethylenglykoly; Magnets; Mice, Nude; myši; ženské pohlaví; Magnetic targeting; lékové transportní systémy; Animals; Optoacoustic imaging; Doxorubicin; Antibiotics, Antineoplastic; počítačová rentgenová tomografie; Ferric Compounds; magnety; Photoacoustic Techniques; Female